2014
DOI: 10.1371/journal.pgen.1004756
|View full text |Cite
|
Sign up to set email alerts
|

The Talin Head Domain Reinforces Integrin-Mediated Adhesion by Promoting Adhesion Complex Stability and Clustering

Abstract: Talin serves an essential function during integrin-mediated adhesion in linking integrins to actin via the intracellular adhesion complex. In addition, the N-terminal head domain of talin regulates the affinity of integrins for their ECM-ligands, a process known as inside-out activation. We previously showed that in Drosophila, mutating the integrin binding site in the talin head domain resulted in weakened adhesion to the ECM. Intriguingly, subsequent studies showed that canonical inside-out activation of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 59 publications
3
27
1
Order By: Relevance
“…In mammalian cells, IPP complex modulates integrin extracellular adhesion for ECM ligands in a talin-or kindlindependent manner (Honda et al, 2009(Honda et al, , 2013Huet-Calderwood et al, 2014). In Drosophila, talin strengthens integrin adhesion by facilitating integrin clustering rather than increasing integrin affinity (Brown et al, 2002;Bunch, 2010;Ellis et al, 2014;Helsten et al, 2008). We tested whether IPP complex facilitates talindependent integrin clustering (Calderwood et al, 2013).…”
Section: Distinct Requirements Of Ipp Complex and Talin In Integrin-mmentioning
confidence: 99%
“…In mammalian cells, IPP complex modulates integrin extracellular adhesion for ECM ligands in a talin-or kindlindependent manner (Honda et al, 2009(Honda et al, , 2013Huet-Calderwood et al, 2014). In Drosophila, talin strengthens integrin adhesion by facilitating integrin clustering rather than increasing integrin affinity (Brown et al, 2002;Bunch, 2010;Ellis et al, 2014;Helsten et al, 2008). We tested whether IPP complex facilitates talindependent integrin clustering (Calderwood et al, 2013).…”
Section: Distinct Requirements Of Ipp Complex and Talin In Integrin-mmentioning
confidence: 99%
“…Specifically, whereas divalent cations were able to induce changes in integrin affinity to its ligands, Talin-mediated inside-out signaling failed to do so (Helsten et al, 2008). Further work has shown that the introduction of a point mutation in Talin that specifically blocked the ability of its head domain to induce inside-out activation but did not impinge on its ability to bind to the integrin cytoplasmic tail did not give rise to a detectable phenotype (Ellis et al, 2014). Taken together, these studies point to a model whereby outside-in integrin activation but not Talin-mediated inside-out integrin activation is present in flies.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguing evidence from Drosophila, using a sensor for integrin activation, has suggested that Mn 2+ might be able to activate integrins in vivo, in larval imaginal discs (Helsten et al, 2008). Moreover, reverse and forward genetic approaches in the fly have identified point mutations in Talin and the β-integrin subunit (known as βPS integrin) that have been proposed to modulate activation (Ellis et al, 2014(Ellis et al, , 2011Jannuzi et al, 2002Jannuzi et al, , 2004Pines et al, 2012Pines et al, , 2011Tanentzapf and Brown, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The impairment of integrin activation by the L325R talin mutation was confirmed by the defects in hematopoietic cells (Stefanini et al, 2014;Yago et al, 2015). In the fly, the R367A talin mutation caused lethality but with a much weaker phenotype than a null allele, whereas no defects were detected with L334R (Tanentzapf and Brown, 2006a;Ellis et al, 2014). Thus, for integrin-mediated adhesion to the ECM within intact tissues it is difficult to make a firm conclusion from current evidence regarding the importance of inside-out activation in general, and the contribution of talin in particular.…”
Section: Box 2 Testing the Importance Of Inside-out Integrin Activatmentioning
confidence: 92%